(untitled) (Acta Scientiarum. Animal Sciences, 2018)
The effects of microcapsule diet as co-feeding for early weaning phase of gourami larvae where evaluated in terms of ingestion rate of microcapsule, growth, and survival rate. The availability of tubifex worms as natural food is uncertain and can introduce pathogens to fish culture from outside environment. Therefore, the attempt to replace or substitute this natural food continues in order to reduce the level of dependence. This research used Complete Randomized Designed (CRD) with four treatments based on a different protocol feeding management. Gourami larvae should be started with the co-feeding on day 12 until day 17 and they are more receptive to microcapsule diets after day 17. The ingestion rate of microcapsule which consumed by the larvae during the period of rearing was 48.33, 68.33, and 88.33%. This study indicated that larvae started co-feeding day 22 showed highest of ingestion rate of the microcapsule, survival rate, specific growth rate and weight gain.